PREFERENSI KONSUMEN TERHADAP KEPUTUSAN MEMBELI MASKER WAJAH MENGGUNAKAN ANALISIS KONJOIN - Stephani Lyana; Tumpal Janji Raja Sitinjak (Jurnal Cakrawala Ilmiah, 2026)
Business competition in the era of globalization is getting bigger, where companies are required to be able to meet increasingly diverse human needs. Cosmetics are a familiar thing and become one of the daily needs. Masks are one of the cosmetic categories used by men and women. The diversity of types of masks is now a consideration for consumers in choosing masks because each consumer has different preference. This study uses preference theory as the main theory. consumer preferences as a choice of likes or dislikes by someone towards the product (goods or services) consumed. Consumer preference shows consumer preferences from a variety of product choices. This study uses a conjoint analysis with the questionnaire instrument. The research data obtained from the questionnaire results of the SPSS syntax in which there is a choice card which is then reprocessed to see the value of the interests and preferences of consumers towards the selection of masks. From the results of the study, consumers prefer face masks that are imported products with the most preferred type of mask, sheet mask, have aroma and use tube or jar packaging, which in one package can be used several times. While the value of its importance is the first type of mask, the second is the origin of the product and the aroma and the last of the packaging. This sequence is the attribute seen by consumers in the selection of facial mask products. The conclusion of this study is that in the selection of face masks, consumers are more likely to see mask types with the most preferred type of mask sheet. Then look at the origin of the product, as long as the most preferred product is imported. Then the value of the next interest is the aroma from the mask where consumers prefer masks that have scents. The last is packaging where consumers prefer in the form of jar / tube where in one package can be used several times.